Behavior-based tariffs in health insurance: Compatibility with the German system - Christine Arentz; Rebekka Rehm (Otto-Wolff-Institut für Wirtschaftsordnung (owiwo), 2016)
In the following, we will analyze the consequences of an implementation of behavior-based tariffs/bonus programs in private and public health insurance in Germany. Programs rewarding a particular behavior have been used in health insurance for years. However, the respective debate has recently been revived as insurers started using so called wearables to monitor the behavior of their insured more accurately.
Keywords: 330